OFW remittances, community, social and personal services and the growth of social capital - Lopez, Leslie Advincula (Philippine Sociological Review, 2005)
Remittances of Overseas Filipino Workers (OFW) constitute one of the most important sources of foreign revenues for the Philippines in the last 30 years. While having the most direct and far-reaching impact on OFW families, remittances seemed to have failed to create a substantial social development impact both at the national level and the community-sending localities. These conclusions stem from the observation that majority of the remittances are spent on consumer durables, dwellings, and education for their children with only a small percentage of remittances being channeled into real productive investments. This study argues that OFWs invest in social and personal services to strengthen their bonds with family and friends, thereby, increasing their social status/security in the community. Drawing on existing case studies of communities with known high concentration of overseas workers, the study examines the social context of OFWs’ spending patterns and shows how these investments make sense if considered within the structure of their social relations. Utilizing the concept of social embeddedness and social capital, the study illustrates that seemingly non-productive investments are actually investments in constructing social capital (e.g., education support for children/relatives, sponsorships in weddings/baptisms, medical assistance for relatives) and the social security of their families left behind as well as when the migrant eventually retires. The results of the study indicate that remittances do have an important role in the development of social capital both at the household and community levels through the expansion of the community’s social and personal services (CSPS).This could enhance the quality of life both at the individual and community levels but could also exacerbate the heavy burden borne by overseas workers